385 Subjective-objective sleep discrepancy and quality of life in self-reported insomnia and sleep apnea. (3rd May 2021) - Ma, Yan; Goldstein, Michael; Davis, Roger; Yeh, Gloria
Abstract: Introduction: Current diagnostic classifications define insomnia based on self-reported sleep difficulties. However, differences between self-reported and objectively measured sleep parameters (subjective-objective sleep discrepancy or sleep misperception) are very common. Insomnia and sleep apnea cause common impairments that overlap and have negative impacts on overall health. Previous studies have encouraged an in-depth understanding of subjective-objective sleep discrepancy to inform a role for behavioral, mind-body approaches to insomnia. In this study, utilizing patients with insomnia and comorbid sleep apnea, we aimed to understand associations between self-reported insomnia, sleep difficulties, sleep misperception and quality-of-life. Methods: We conducted a secondary analysis using data from the Sleep Heart Health Study (a multi-site nationally representative sample) to examine the profile of subjective and objective sleep measures in people with insomnia (IS, n=73) and comorbid sleep apnea (IS+SA, n=143), compared to individuals with sleep apnea only (SA, n=296) and normal sleep controls (NSC, n=126). We also compared the magnitude of sleep misperception between these four groups and examined the corresponding impact of subjective insomnia complaints on quality-of-life. Results: Sleep discrepancy was found in all four groups. After controlling for age, sex, mental health conditions, sleep apnea severity, and objectively measured sleep time, the presence of self-reported insomnia had the strongest association with sleep discrepancy on total sleep time (TST, β=-34.4, p<0.001) and sleep onset latency (SOL, β=14.7, p<0.001). Subjects who reported no difficulty falling asleep slightly underestimated their sleep onset latency, while those who reported difficulty substantially overestimated sleep latency. Self-reported insomnia had a significantly negative impact on the quality of life in both physical and mental components (p<0.001). Conclusion: Sleep discrepancy exists in normal controls, insomnia, and sleep apnea. Subjects with self-reported insomnia have a higher degree of sleep misperception. Both sleep apnea and self-reported insomnia are associated with negative QOL. Those with comorbid sleep apnea report the greatest sleep discrepancy and lowest QOL. Further research is needed to better understand individual profiles of misperception and insomnia phenotypes, apnea comorbidity and quality-of-life. Behavioral, mind-body interventions may offer strategies to address mental stress, sleep misperception, and insomnia. Support (if any): NCCIH T32AT000051 and NHLBI 5T32HL007901-22